Pemeriksaan Residu Pestisida Profenofos pada Selada (Lactuca sativa L.) dengan Metode Kromatografi Gas - Yohannes Alen; Zulhidayati Zulhidayati; Netty Suharti (Fakultas Farmasi Universitas Andalas, 2015)
The determination of profenofos pesticidal residue in the lettuce (Lactuca sativa L.) by using gas chromatography using flame photometric detector (FPD) had been investigated. The lettuce was collected from Padang Luar area, Agam distric, West Sumatera. Sample for determination of profenofos residue divided into three groups: unwashed (A), washed with water (B), and washed with detergent (C). Maceration with sonication was used for the extraction using ethylacetateas a solvent. The results showed that profenofos pesticide residue in sample A, B and C were 0.204, 0.080 and 0.061 ppm, respectively. These profenofos pesticidal residue are over than the Maximum Residue Limits (MRL) that established by The Japan Food Chemical Research Foundation (0.05 ppm) even though World Health Organization (WHO) has not established Maximum Residue Limits (MRL) profenofos on lettuce. Based on the statistical analysis one-way method (Anova) using SPSS 20.0 showed that there was a significant concentrations difference between lettuce A from lettuce B and lettuce C with p < 0.05.